A novel group authentication for RuBee sensors in wireless sensor networks. (29th June 2011) - Wu, Tin-Yu; Chen, Whai-En; Chan, Hung-Lin
4G, the new generation mobile communication, will be formed among heterogeneous wireless networks, which include Wi-Fi, WPAN, etc. At the beginning of 2007, IEEE developed the new short-distance transmitting standard, IEEE1902.1, also known as RuBee. Therefore, the purpose of this paper is to investigate how RuBee sensors transmit data through the sensor networks provided by worldwide interoperability for microwave access (WiMAX). Nevertheless, some problems still need to be solved: for instance, how to integrate AAA procedure; the lack of problem of IPv4 IP number and the classification of every RuBee sensor. To solve these problems, we propose gateway access point (GAP) to deal with signal transmission and transformation of both ends. GAP can substitute RuBee for group authentication from remote authentication dial in user service (RADIUS) of WiMAX, and classify and manage each RuBee sensor. Our proposed scheme can easily attain security, group anthentication and improvement in handoff.